Analytical method for calculation of cogging torque reduction due to slot shifting in a dual stator dual rotor permanent magnet machine with semi-closed slots - Kumar P.; Reza M.M.; Srivastava R.K. (My University, 2025)
Radial flux Dual Stator Dual Rotor Permanent Magnet (DSDRPM) machine can be considered as an exterior rotor Permanent Magnet (PM) machine kept over an interior rotor PM machine. This facilitates with a scope for optimization of the relative placement of inner and outer stator slots of the machines to achieve cogging torque minimization. This paper deals with the analytical prediction of flux density distribution in an internal and external rotor PM machines with semi-closed slots and further utilizes it to calculate the cogging torque in DSDRPM machine. An optimal angle of shift between the stator slots of the two machines has been determined to obtain a reduction in the resultant cogging torque of DSDRPM machine. The analytical results are verified with the Finite Element Analysis (FEA) results and found to be in close agreement with each other. © 2018, Electromagnetics Academy. All rights reserved.